Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan Pada CV RGSB Berkah Jaya Garut - Nizar Alam Hamdani (Jurnal Wacana Ekonomi, 2016)
Employees are a very important resource for the survival of the company, so it is necessary to pay attention to matters relating to employee performance in order to achieve company goals. The purpose of this study was to determine the effect of compensation and work environment on employee performance at CV. RGSB Blessing Jaya Garut. The sample in this study were employees who worked at CV. RGSB Berkah Jaya Garut, as many as 55 people. The sampling technique is saturated or census technique. The data analysis used is the multiple regression analysis technique using SPSS software. The results of the analysis in this study indicate that H1 there is an effect of compensation and work environment simultaneously on employee performance at CV. RGSB Berkah Jaya Garut, then H2 there is an effect of compensation on employee performance at CV. RGSB Berkah Jaya Garut, and H3 there is an influence of the work environment on employee performance at CV. RGSB Blessing Jaya Garut.